A Proposal to Improve Business Performance of CV Seruni Snack Through Better Production Method and Employee Engagement - Heryana, Agni Luthfi; Saksono, Prasetyo Budi (The Indonesian Journal of Business Administration, 2013)
â€” Snack industry has a rapid growth today. One industry that is involved in snack industry is CV Seruni Snack. CV Seruni Snack is a producer of Palembang Crackers. Last several months ago, CV Seruni Snack faced some problem. One symptom that emerge from the problems encountered by CV Seruni Snack is there are a lot of employees who resigned in recent months. From the interview, it was found that most of the employees have a low engagement level. This low engagement level caused by two things, that are inadequate salary and lack of business ownerâ€™s attention. The company itself cannot provide an adequate wages to their employees because of the small profits that it got from the Palembang Crackers production activity. This paper propose the solution to overcome the problems of CV Seruni Snack from two sides, that are operational and human resource management. From the operational side, improvement of the production method is proposed to increase the effectivity and the efficiency of the production process so the profit will increase. From human resource management side, this paper propose the implementation of piece rate wage system, leadership practices according to Kouzes and Posner, and job rotation.Â Key words: engagement, piece rate wage system, leadership practices